Does spirituality predict death anxiety in chronically ill older adults in a religious context? - Rezaei Aderyani, Mohsen (Journal of religion, spirituality & aging, 2021)
Spirituality can be considered as a source of making meaning in life and may be important effect in defeating the fear of death. The aim of the study was to determine the predictors of death anxiety based on spirituality components in older adults with chronic disease. One hundred and fifty Iranian patients over 60 years old were selected by convenience sampling. The functional assessment of chronic illness therapy-Spiritual Well-being Scale, hospital anxiety and depression scale, and death anxiety scale was used for data collection. Results of multiple linear regression analysis showed that faith (β =−0.27; p = .038), and anxiety (β = 0.30; p = .018) had a significant relationship with death anxiety. Strengthening spirituality such as faith-Based health intervention may be helpful in patients with symptoms of death anxiety.